A composite structure containing four layers of gradient energy absorption and a preparation method and application thereof

By using a four-layer gradient energy-absorbing composite structure, the problems of insufficient interlayer bonding strength and easy deformation of anti-corrosion coating in multi-layer composite bottom protection plates are solved, realizing a high-strength, corrosion-resistant automotive bottom protection plate design, which is suitable for bottom protection of battery packs in new energy vehicles.

CN123040429APending Publication Date: 2026-11-06CHINA MASCH PRECISION FORMING IND TECH RES INST (ANHUI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611537052.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-30
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing multi-layer composite bottom protection plates have insufficient interlayer bonding strength, and the anti-corrosion coating is prone to deformation under high impact deformation conditions, leading to interlayer debonding, delamination and anti-corrosion failure.

Method used

The four-layer gradient energy-absorbing composite structure consists of a polyurea elastic buffer layer, a high-strength steel layer, an ultra-fine fully glued honeycomb aluminum layer, and a PA fiberglass backing layer, from the outside to the inside. Through polyurethane electrophoretic anti-corrosion layer, vacuum potting and hot-pressing composite technology, a gradient energy-absorbing synergistic structure is formed, which enhances the interlayer adhesion and anti-corrosion performance.

Benefits of technology

It improves the interlayer bonding strength, prevents delamination and separation of interlayers under high impact, maintains the continuity of anti-corrosion performance, extends the structural life, and enhances impact resistance and anti-corrosion ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123040429A_ABST
    Figure CN123040429A_ABST
Patent Text Reader

Abstract

This invention relates to the field of composite material technology, and discloses a four-layer gradient energy-absorbing composite structure, its preparation method, and its application. From the outside in, this structure comprises a polyurea elastic buffer layer, a high-strength steel layer, an ultrafine fully adhesive honeycomb aluminum layer, and a PA fiberglass backing layer. A polyurethane electrophoretic anti-corrosion layer is provided on the outer surface of the high-strength steel layer. The ultrafine fully adhesive honeycomb aluminum layer is disposed between the high-strength steel layer and the PA fiberglass backing layer, with the honeycomb cavity filled with resin colloid. The polyurea elastic buffer layer is disposed on the outer surface of the polyurethane electrophoretic anti-corrosion layer. The four layers form a progressively transferring gradient energy-absorbing synergistic structure. The fully adhesive filling of this invention transforms the interlayer contact from surface contact to volume contact, improving the interlayer bonding strength. The polyurethane electrophoretic anti-corrosion layer extends synchronously with the deformation of the high-strength steel layer, maintaining the integrity of anti-corrosion after impact. This structure is suitable for bottom protection of battery packs in new energy vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of composite material technology, specifically to a composite structure containing four layers of gradient energy absorption, its preparation method, and its application. Background Technology

[0002] With the development of the new energy vehicle industry, the bottom protection of power battery packs is receiving increasing attention. Battery packs are typically located under the vehicle's floor and may be subjected to impacts from flying stones, balls, and scrapes during vehicle operation. Relevant safety standards require that the underbody protection plate not penetrate under high-energy impacts to prevent deformation of the battery pack casing or damage to the battery cells. Furthermore, the underbody protection plate is constantly exposed to mud, water, and salt spray environments, requiring long-term corrosion resistance.

[0003] However, existing multi-layer composite bottom linings have the following problems in terms of interlayer bonding and corrosion protection: (1) Regarding interlayer bonding, the bonding between multilayer structures mostly relies on surface adhesive or local adhesive bonding processes. The adhesive layer only covers part of the interface, and the bonding contact area is limited. When subjected to high-energy impact, the interlayer interface is subjected to large shear and peel stress. Insufficient bonding strength can easily lead to interlayer debonding, hollowing, or even delamination, making the multilayer structure unable to dissipate energy in a coordinated manner and significantly reducing its impact resistance.

[0004] (2) In terms of corrosion protection, the surface of the metal layer of the existing bottom plate is usually coated with anti-corrosion coating. However, traditional anti-corrosion coatings are mostly rigid systems with limited elongation at break. When the metal substrate undergoes local plastic deformation under high impact, the coating is difficult to extend synchronously with the substrate, and is prone to cracking, paint chipping or peeling, resulting in discontinuity of the anti-corrosion shielding layer. Corrosive media can penetrate from the damaged area, causing anti-corrosion failure after impact.

[0005] In summary, existing multi-layer composite bottom plates still need improvement in the following aspects: the interlayer bonding strength between the multi-layer structures needs to be improved to avoid interlayer debonding and delamination under high impact conditions; the integrity of the anti-corrosion coating under high impact deformation conditions needs to be guaranteed to maintain long-term anti-corrosion performance after impact. Summary of the Invention

[0006] The purpose of this invention is to provide a composite structure containing four gradient energy absorption layers, its preparation method and application, in order to solve the technical problems of insufficient interlayer bonding strength between multilayer structures and easy deformation of anti-corrosion coatings under high impact deformation conditions in the prior art.

[0007] To solve the above-mentioned technical problems, the present invention specifically provides the following technical solution: A composite structure containing four gradient energy absorption layers, from the outside to the inside, includes: a polyurea elastic buffer layer, a high-strength steel layer, an ultra-fine fully glued honeycomb aluminum layer, and a PA fiberglass backing layer. The outer surface of the high-strength steel layer is provided with a polyurethane electrophoretic anti-corrosion layer; The ultra-fine fully glued honeycomb aluminum layer is disposed between the high-strength steel layer and the PA fiberglass backing layer, and the honeycomb cavity of the ultra-fine fully glued honeycomb aluminum layer is filled with resin colloid. The polyurea elastic buffer layer is disposed on the outer surface of the polyurethane electrophoretic anti-corrosion layer; The polyurea elastic buffer layer, the high-strength steel layer, the ultrafine fully glued honeycomb aluminum layer, and the PA fiberglass backing layer form a gradient energy absorption synergistic structure that transfers energy step by step.

[0008] Furthermore, the thickness of the polyurea elastic buffer layer is 0.5-1.2 mm; The thickness of the high-strength steel layer is 1.0-2.0 mm; The thickness of the polyurethane electrophoretic anti-corrosion layer is 30-50 μm; The ultrafine fully coated honeycomb aluminum layer has a pore size of 0.3-0.8 mm and a thickness of 2.5-4.5 mm after compression.

[0009] Furthermore, the resin colloid is epoxy resin or polyurethane resin; the PA fiberglass backing layer is a PA fiberglass backing layer.

[0010] This invention further discloses a method for preparing a four-layer gradient energy-absorbing composite structure, comprising the following steps: S100. Provide a high-strength steel substrate, and perform polyurethane cathodic electrophoresis treatment on the outer surface of the high-strength steel substrate to form a polyurethane electrophoretic anti-corrosion layer, so as to obtain a high-strength steel layer. S200. Provide ultra-fine honeycomb aluminum, compress and shape the ultra-fine honeycomb aluminum, and then perform vacuum potting to fill the honeycomb cavity with resin colloid to form an ultra-fine fully glued honeycomb aluminum layer. S300. Spray polyurea on one side of the high-strength steel layer to form a polyurea elastic buffer layer, and bond the ultra-fine full-adhesion honeycomb aluminum layer to the other side of the high-strength steel layer to obtain a three-layer composite material. S400. The PA fiberglass backing layer is hot-pressed onto the ultrafine fully glued honeycomb aluminum layer of the three-layer composite material to obtain a four-layer gradient energy-absorbing composite structure.

[0011] Furthermore, in step S200, the pore size of the ultrafine honeycomb aluminum is 0.3-0.8mm, and the overall thickness after compression is 2.5-4.5mm; the vacuum degree of the vacuum potting is -0.05~-0.098MPa, so that there are no continuous through cavities in the honeycomb cavity and no areas of missing glue visible to the naked eye. The fill rate of the honeycomb cavity is ≥95%.

[0012] Further, in step S200, the vacuum potting includes the following sub-steps: S201. Take the resin colloid, add 5-8% wetting and dispersing agent based on the total mass of the resin colloid, stir evenly, and then perform vacuum degassing treatment. The vacuum degree is -0.09--0.098MPa, and the treatment is maintained for 30-60 minutes. S202. After the ultra-fine honeycomb aluminum compressed to the target thickness is left to stand for 10-30 minutes under the constraint of the mold, the elastic rebound of the aluminum foil is fully released and the honeycomb wall reaches a stable geometric configuration before the glue is poured. S203. Place the settled ultra-fine honeycomb aluminum into the vacuum potting chamber. The potting port is set at the bottom of the ultra-fine honeycomb aluminum, and the outlet is set at the top. Under vacuum negative pressure, the adhesive is pushed upward from the bottom and the air is discharged from the top. During the dispensing process, a stepped vacuum is used: the first stage vacuum is -0.03~-0.05MPa and maintained for 60-90s, the second stage vacuum is -0.05~-0.06MPa and maintained for 60-90s, and the third stage vacuum is -0.09~-0.098MPa and maintained for 120-180s; the dispensing speed is controlled at 5~15mm / min.

[0013] Furthermore, during the glue-filling process in step S203, low-frequency micro-vibration is applied to the bottom of the vacuum glue-filling cavity. The vibration frequency is 20-50Hz and the amplitude is in the micrometer range, in order to reduce the wall friction resistance when the glue moves forward in the ultra-fine honeycomb cavity and promote the glue to pass through the necking area.

[0014] Further, in step S100, the thickness of the polyurethane cathodic electrophoresis deposited film is 30-50 μm, and the drying temperature is 160-180℃. In step S300, the spraying is high-pressure airless spraying, with multiple thin layers superimposed. The thickness of a single spray is 0.1-0.4 mm, and the cumulative total thickness is 0.5-1.2 mm. The construction environment temperature is 20-30℃, the interval between each spray is 10-20 minutes, and the curing time is 30-60 minutes at room temperature. The bonding and lamination process is as follows: integral roller pressing lamination at 0.2-0.6MPa, and low-temperature pre-curing at 60-80℃ for 60-120 minutes; In step S400, the hot pressing temperature is 65-85℃, the pressure is 0.3-0.5MPa, and the pressure holding time is 40-90min; after the composite is completed, it is kept at a constant temperature for 12-36h.

[0015] Application of a four-layer gradient energy-absorbing composite structure or its preparation method in automotive underbody protection plates, wherein the automotive underbody protection plates are used for bottom protection of battery packs in new energy vehicles.

[0016] Furthermore, the four-layer gradient energy-absorbing composite structure is installed with the polyurea elastic buffer layer facing the outside of the vehicle and the PA fiberglass backing layer facing the inside of the vehicle compartment.

[0017] Compared with the prior art, the present invention has the following advantages: This invention provides a four-layer gradient synergistic energy-absorbing material. The polyurea elastic buffer layer first absorbs external impacts, diffusing point loads into surface loads through elastic deformation, pre-dissipating part of the impact kinetic energy. The high-strength steel layer absorbs the surface loads and expands the stress area, uniformly introducing the load into the honeycomb layer. The ultra-fine fully adhesive honeycomb aluminum layer dissipates energy through the progressive plastic buckling of the aluminum foil and the extrusion deformation of the resin colloid in the cavity. The PA fiberglass backing layer forms a constraint and support at the bottom of the honeycomb, inhibiting its lateral expansion and breakage. The four layers form a gradient energy-absorbing synergistic structure that transmits energy step by step, weakening the impact load along the transmission path, which is beneficial for achieving a high level of ball impact protection within a limited thickness.

[0018] The polyurethane electrophoretic anti-corrosion layer of this invention is applied to the outer surface of a high-strength steel layer. Its flexible chain segment structure gives the coating a high elongation at break. When the high-strength steel layer undergoes local micro-plastic deformation under impact, the anti-corrosion layer can extend synchronously with the substrate, making it less prone to cracking or peeling. Thus, it maintains a continuous and complete anti-corrosion shielding layer after impact, which is beneficial to extending the service life of the structure in corrosive environments.

[0019] The adhesive injection process provided by this invention can obtain an ultra-fine, fully adhesive-coated honeycomb aluminum layer, transforming the bonding between the honeycomb layer and the high-strength steel layer and PA fiberglass backing layer from the localized surface contact of the traditional surface adhesive process to a full-area body contact. This significantly increases the bonding contact area, resulting in a more uniform distribution of interfacial stress. The number of continuous through cavities within the honeycomb cavity is reduced, minimizing unbonded areas at the interface. This helps suppress interlayer debonding and delamination under high-impact conditions. Simultaneously, the honeycomb aluminum foil receives internal support from the adhesive within the cavity during buckling and collapse, making the energy absorption process more gradual and stable. Attached Figure Description

[0020] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings in the following description are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.

[0021] Figure 1 This is a schematic diagram of the overall structure provided for an embodiment of this application.

[0022] Figure 2 This is a schematic diagram of the internal structure of the ultra-fine fully coated honeycomb aluminum layer provided in the embodiments of this application.

[0023] Figure 3 This is a schematic diagram of the front structure of the PA fiberglass backing layer provided in the embodiments of this application.

[0024] Figure 4 This is a schematic diagram of the method flow provided in the embodiments of this application.

[0025] The reference numerals in the figure are as follows: 1-Polyurea elastic buffer layer; 2-High-strength steel layer; 3-Ultra-fine fully glued honeycomb aluminum layer; 4-PA fiberglass backing layer; 5-Polyurethane electrophoretic anti-corrosion layer. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0027] like Figures 1 to 3 As shown, the present invention provides a composite structure containing four gradient energy absorption layers, characterized in that, from the outside to the inside, it comprises: a polyurea elastic buffer layer 1, a high-strength steel layer 2, an ultra-fine fully glued honeycomb aluminum layer 3, and a PA fiberglass backing layer 4.

[0028] The outer surface of the high-strength steel layer 2 is provided with a polyurethane electrophoretic anti-corrosion layer 5.

[0029] The ultrafine fully adhesive honeycomb aluminum layer 3 is disposed between the high-strength steel layer 2 and the PA fiberglass backing layer 4, and the honeycomb cavity of the ultrafine fully adhesive honeycomb aluminum layer 3 is filled with resin colloid.

[0030] The polyurea elastic buffer layer 1 is disposed on the outer surface of the polyurethane electrophoretic anti-corrosion layer 5.

[0031] The polyurea elastic buffer layer 1, the high-strength steel layer 2, the ultrafine fully coated honeycomb aluminum layer 3, and the PA fiberglass backing layer 4 form a gradient energy absorption synergistic structure that transmits energy step by step. When the polyurea elastic buffer layer 1 is subjected to external impact, it undergoes elastic deformation, diffusing the point impact load into a surface load and transferring it to the high-strength steel layer 2. When the high-strength steel layer 2 bears the surface load, it undergoes localized micro-plastic deformation to expand the stress area and uniformly distribute the load to the ultrafine fully coated honeycomb aluminum layer 3.

[0032] When the ultrafine fully adhesive honeycomb aluminum layer 3 bears a load, its honeycomb aluminum foil undergoes progressive plastic buckling and collapse, while the resin colloid undergoes extrusion deformation. The two work together to dissipate impact energy. When the ultrafine fully adhesive honeycomb aluminum layer 3 buckles and collapses, the PA fiberglass backing layer 4 applies a restraint to the bottom of the ultrafine fully adhesive honeycomb aluminum layer 3, inhibiting its lateral expansion and cracking.

[0033] Throughout the entire transmission process of the external impact, the polyurethane electrophoretic anti-corrosion layer 5 extends synchronously with the deformation of the high-strength steel layer 2, maintaining the interfacial adhesion between the high-strength steel layer 2, the polyurea elastic buffer layer 1, and the ultra-fine full-adhesion honeycomb aluminum layer 3.

[0034] The four-layer gradient energy-absorbing composite structure can be used as an automotive underbody protection plate for the bottom protection of battery packs in new energy vehicles. It is installed with the polyurea elastic buffer layer 1 facing the outside of the vehicle and the PA fiberglass backing layer 4 facing the inside of the vehicle compartment.

[0035] Specifically, in this invention, when a vehicle passes through a road at high speed, if an external impact object (such as a flying stone, a ball, etc.) hits the outermost polyurea elastic buffer layer 1, the polyurea elastic buffer layer 1 first undergoes elastic deformation through its own high elasticity and high toughness characteristics, spreading the point impact load to the surrounding area and the edge area of ​​the structure, and transferring it to the high-strength steel layer 2, thus completing the first stage of flexible buffering and pre-dissipation of impact kinetic energy.

[0036] The high-strength steel layer 2 bears the surface load diffused by the polyurea elastic buffer layer 1. It expands the stress area through its own rigid bearing and local micro-plastic deformation, avoids local stress concentration, and uniformly introduces the load into the inner compressed ultra-fine full-adhesion honeycomb aluminum layer 3.

[0037] The compressed ultrafine fully glued honeycomb aluminum layer 3 undergoes multi-stage progressive plastic buckling and collapse under load, and the honeycomb aluminum foil undergoes plastic deformation. At the same time, the resin colloid filled in its cavity undergoes compression, shearing and friction energy dissipation, forming a composite energy absorption path, thereby continuously and stably dissipating impact energy.

[0038] During the compression and energy absorption process of the ultra-fine fully glued honeycomb aluminum layer 3, it is prone to lateral expansion, unit breakage, or boundary instability. At this time, the PA fiberglass backing layer 4, which is attached to the inner side of the honeycomb aluminum layer, forms a continuous bottom restraint and limiting support for the bottom of the honeycomb aluminum layer, inhibiting excessive expansion, breakage, and impact penetration of the honeycomb units, and ensuring that the honeycomb aluminum layer maintains the integrity of the overall structure after energy absorption.

[0039] Furthermore, the polyurethane electrophoretic anti-corrosion layer 5 is disposed on the surface of the high-strength steel layer 2, forming a flexible interface transition layer between the high-strength steel layer 2 and the outer polyurea elastic buffer layer 1 and the inner compressed ultrafine full-adhesion honeycomb aluminum layer 3, which has the triple functions of anti-corrosion shielding, interface bonding and deformation following.

[0040] 1. Corrosion Protection and Shielding: The polyurethane electrophoretic anti-corrosion layer 5 forms a physical barrier against corrosive media such as water, oxygen, and chloride ions, blocking their penetration paths to the steel substrate surface. Simultaneously, the outer side of this layer is fully bonded to the polyurea elastic buffer layer 1, and the inner side is fully bonded to the ultra-fine fully adhesive honeycomb aluminum layer 3, minimizing gaps and voids, thus eliminating as many channels as possible for corrosive media to penetrate along the interlayer interfaces.

[0041] 2. Interface bonding: The cavity of the compressed ultrafine full-adhesion honeycomb aluminum layer 3 is fully filled with adhesive, which changes the traditional surface contact between the honeycomb layer and the high-strength steel layer 2 and PA fiberglass backing layer 4 to a body contact. The bonding contact area is significantly increased, eliminating the weak area of ​​the cavity interface. Combined with the flexible interface transition of the polyurethane electrophoretic anti-corrosion layer 5, it is used to suppress interlayer peeling and interface debonding under high impact conditions.

[0042] 3. Deformation following: The polyurethane electrophoretic anti-corrosion layer 5 has a high elongation at break, which can extend synchronously with the local micro-stretching and micro-depression plastic deformation of the high-strength steel layer 2. During the impact process, the polyurethane electrophoretic anti-corrosion layer 5 extends and deforms synchronously with the high-strength steel layer 2, maintaining continuous bonding and anti-corrosion shielding at the interface, inhibiting relative misalignment between the high-strength steel layer 2 and adjacent functional layers, coating cracking and interlayer peeling, and extending the anti-corrosion service life of the structure.

[0043] The four-layer structure is tightly bonded, making it less prone to hollowing, and the full-area bonding forms an integrated composite structure, which can improve the overall fatigue resistance, impact resistance of gravel, and long-term structural stability of composite materials, and reduce stress concentration, instantaneous collapse and interlayer failure problems.

[0044] The thickness of the polyurea elastic buffer layer 1 is 0.5-1.2 mm, the thickness of the high-strength steel layer 2 is 1.0-2.0 mm, the thickness of the polyurethane electrophoretic anti-corrosion layer 5 is 30-50 μm, and the honeycomb pore size of the ultrafine fully glued honeycomb aluminum layer 3 is 0.3-0.8 mm, with a thickness of 2.5-4.5 mm after compression.

[0045] Preferably, the polyurea elastic buffer layer 1 has a thickness of 0.9 mm, the high-strength steel layer 2 has a thickness of 1.5 mm, the polyurethane electrophoretic anti-corrosion layer 5 has a thickness of 40 μm, and the ultrafine fully glued honeycomb aluminum layer 3 has a honeycomb pore size of 0.5 mm and a thickness of 3.4 mm after compression.

[0046] The 0.5mm ultra-fine pore size of the honeycomb aluminum significantly increases the number of honeycomb units and the energy absorption level, extends the impact collapse deformation stroke, and the full glue filling gives the honeycomb cavity a dual energy absorption path of aluminum foil plastic deformation and resin extrusion deformation, avoiding instantaneous instability and collapse of the honeycomb structure, making the energy absorption process more gradual and stable.

[0047] The resin colloid is epoxy resin or polyurethane resin, and the PA fiberglass backing layer 4 is a PA fiberglass backing layer 4.

[0048] PA fiberglass backing layer 4, as a thermoplastic recyclable backing layer, has better toughness than traditional thermosetting fiberglass boards. It can absorb energy through slight deformation during impact, making it less prone to brittle cracking. At the same time, it has melt-reconstruction properties, enabling the entire underbody panel to meet the requirements for the recyclability of automotive parts.

[0049] The combination of ultra-fine honeycomb aluminum and thermoplastic PA fiberglass backing can reduce structural weight while ensuring high ball impact resistance, and also take into account material recyclability, thus meeting the requirements of lightweighting and environmental protection policies for new energy vehicles.

[0050] The existing honeycomb sandwich structure has a low colloid content because the potting process typically involves filling each cell individually with colloid using a scraper and glue gun, followed by drying and curing. This method is inefficient, and air bubbles remain inside the colloid after drying, resulting in poor potting effect and low rigidity. More importantly, due to the high viscosity of the potting compound and the small size and large number of honeycomb cells, the honeycomb potting area is difficult to completely fill; gas is easily trapped within the potting compound, leading to numerous air bubbles. Because of the fluidity of the potting material after mixing, if it cannot completely fill the honeycomb core cells in one go under unconstrained conditions, air will inevitably be trapped inside. During curing, incomplete gas expulsion leaves collapsed air bubbles inside and on the surface of the potting material.

[0051] The adhesion between the collapsed lattice-like material and the planar polyurethane electrophoretic anti-corrosion layer 5 is poor. To maintain the interfacial composite effect, such as... Figure 4 As shown, the present invention also provides a method for preparing a four-layer gradient energy-absorbing composite structure, comprising the following steps: S100. Provide a high-strength steel substrate, and perform polyurethane cathodic electrophoresis treatment on the outer surface of the high-strength steel substrate to form a polyurethane electrophoretic anti-corrosion layer 5, so as to obtain a high-strength steel layer 2. S200. Provide ultra-fine honeycomb aluminum, compress and shape the ultra-fine honeycomb aluminum, and then perform vacuum potting to fill the honeycomb cavity with resin colloid to form an ultra-fine fully glued honeycomb aluminum layer 3. S300. Spray polyurea on one side of the high-strength steel layer 2 to form a polyurea elastic buffer layer 1. Then, bond the ultra-fine fully glued honeycomb aluminum layer 3 to the other side of the high-strength steel layer 2 to obtain a three-layer composite material. S400, PA fiberglass backing layer 4 is hot-pressed onto the ultrafine fully glued honeycomb aluminum layer 3 of the three-layer composite material to obtain a four-layer gradient energy-absorbing composite structure.

[0052] Unlike existing technologies, S200 is fully glued, which changes the bonding between the honeycomb cavity and the high-strength steel layer 2 and PA fiberglass backing layer 4 from traditional surface contact to body contact, significantly increasing the bonding contact area.

[0053] In step S200, the ultrafine honeycomb aluminum blank is in its original pore size state before compression and needs to be compressed to the target thickness at a constant speed through a closed mold. During the compression process, the honeycomb wall undergoes plastic buckling, and the cross-sectional shape of the cavity changes from a regular hexagon to an irregular shape.

[0054] The core objective of potting is to achieve complete filling of the resin colloid within an ultra-fine cavity of 0.3-0.8 mm. The potting process is challenging, as the cross-sectional area of ​​a single cavity with a 0.3 mm pore diameter is only 0.07 mm². 2 When the adhesive flows in such a narrow channel, the frictional resistance on the wall is extremely high; at the same time, the residual air in the cavity is "locked" in the dead corner of the cavity due to surface tension under normal pressure or low vacuum conditions, and cannot float up and be discharged.

[0055] In this step, the invention employs vacuum injection, utilizing negative pressure to reduce the residual air pressure within the cavity, allowing the adhesive to enter the cavity under pressure differential. The adhesive is propelled upwards from the bottom of the honeycomb block in a vacuum environment, while air is expelled from the top. The flow direction of the adhesive is consistent with the air expulsion direction, reducing the problem of air flowing backwards through the adhesive and forming bubbles as in atmospheric pressure injection.

[0056] In this invention, the pore size of the ultrafine honeycomb aluminum is 0.3-0.8mm, and the overall thickness after compression is 2.5-4.5mm; the vacuum degree of the vacuum potting is -0.05~-0.098MPa, so that there are no continuous through cavities in the honeycomb cavity and no areas of missing glue visible to the naked eye, and the filling rate of the honeycomb cavity is ≥95%.

[0057] This invention reduces the pore size of honeycomb aluminum from the conventional 3-6mm to 0.3-0.8mm, increases the number of honeycomb cells per unit area by tens of times, significantly increases the number of honeycomb walls participating in plastic buckling under impact load, and significantly improves the energy absorption level.

[0058] After compression, the overall thickness is controlled at 2.5-4.5mm, which can provide sufficient collapse deformation stroke for the honeycomb aluminum within a limited space.

[0059] In particular, the ultra-fine pore size significantly increases the specific surface area of ​​the honeycomb aluminum, thereby increasing the contact area between the honeycomb wall and the resin colloid. Under full resin filling conditions, this increase in specific surface area directly translates into an increase in the bonding contact area between the honeycomb layer and the high-strength steel layer 2 and the PA fiberglass backing layer 4, which can reach 8-12 times that of traditional surface adhesive processes.

[0060] The core of vacuum potting is to use negative pressure to reduce the residual air pressure inside the honeycomb cavity, allowing the adhesive to enter the cavity under the pressure difference. The vacuum level is in the range of -0.05 to -0.09 MPa to ensure sufficient impregnation and maintain the stability of the adhesive.

[0061] Establishing an air exhaust path: Under vacuum negative pressure, the adhesive flows upward from the bottom of the honeycomb block, while air is exhausted from the top. This ensures that the flow direction of the adhesive is consistent with the air exhaust direction, reducing the problem of air flowing backward through the adhesive and forming bubbles. In actual production, it is necessary to maintain a stable vacuum level to ensure that residual air in the cavity can be continuously extracted, rather than being trapped by the adhesive and forming closed bubbles.

[0062] The ultrafine, fully adhesive-coated honeycomb aluminum layer 3 of this invention has a resin filling rate of ≥95% and no continuous through-cavities. This means that the bonding interface between the honeycomb cavity and the high-strength steel layer 2 and PA fiberglass backing layer 4 is transformed from localized point contact in traditional surface adhesive processes to full-area volume contact. The significant increase in the bonding contact area eliminates stress concentration weak areas at the cavity interface. Under high-impact conditions, the impact load is transferred to the interface through the honeycomb wall and the adhesive within the cavity, resulting in a more uniform interface stress distribution and a significant reduction in the driving force for interlayer delamination. The absence of any visible adhesive gaps ensures that there are no unbonded areas at the interface, preventing interface cracks from initiating and propagating from these gaps during impact.

[0063] If a continuous, through-cavity exists, the impact load will preferentially transfer along that cavity, creating localized stress concentration. This leads to premature instability of the honeycomb wall in that area, resulting in a sudden load drop during the energy absorption process. A fill rate of ≥95% and the absence of continuous, through-cavities make the energy absorption efficiency predictable.

[0064] Preferably, the pore size of the ultrafine honeycomb aluminum is 0.5 mm, and the overall thickness after compression is 3.4 mm; the vacuum degree of the vacuum potting is -0.08 MPa.

[0065] The 0.3-0.8mm ultrafine pore size used in this invention has a cavity cross-sectional area that is only a fraction of that of conventional honeycomb, which drastically increases the resistance to adhesive flow and makes it much more difficult to remove air bubbles. Existing potting processes cannot be directly applied to this invention.

[0066] Meanwhile, the molding quality of the honeycomb core is greatly affected by the process conditions during compression molding. The main impact is that the honeycomb core is wrinkled or even collapsed, causing the entire honeycomb sandwich structure to become unstable and unusable. For ultra-fine pore honeycombs, the honeycomb walls are thinner and the cells are denser, making it more difficult to control the uniform buckling of the honeycomb walls during compression molding. The release process of elastic rebound after compression is also more likely to lead to uncontrollable changes in the geometric configuration.

[0067] To address this issue, the primary obstacle in ultrafine honeycomb potting during actual production is the dissolved gas carried by the adhesive itself. Epoxy resin dissolves a large amount of air during stirring and transport; if this air is not removed beforehand, it forms microbubbles during curing after being poured into the honeycomb cavity. These microbubbles, with a pore size of 0.3 mm, are sufficient to block the entire cavity cross-section.

[0068] Furthermore, the cross-sectional area of ​​a single cavity with a 0.3mm aperture is only 0.07mm².2 The viscous resistance is extremely high when air is expelled in such a narrow channel. When vacuuming at a single vacuum level, tiny air bubbles may be trapped in dead corners of the cavity due to surface tension and cannot rise and escape.

[0069] Therefore, the present invention proposes a sub-step of step S200, which includes the following steps: S201. Take the resin colloid, add 5-8% wetting and dispersing agent based on the total mass of the resin colloid, stir evenly, and then perform vacuum degassing treatment. The vacuum degree is -0.09--0.098MPa, and the treatment is maintained for 30-60 minutes. S202. After the ultra-fine honeycomb aluminum compressed to the target thickness is left to stand for 10-30 minutes under the constraint of the mold, the elastic rebound of the aluminum foil is fully released and the honeycomb wall reaches a stable geometric configuration before the glue is poured. S203. Place the settled ultra-fine honeycomb aluminum into the vacuum potting chamber. The potting port is set at the bottom of the ultra-fine honeycomb aluminum, and the outlet is set at the top. Under vacuum negative pressure, the adhesive is pushed upward from the bottom and the air is discharged from the top. During the dispensing process, a stepped vacuum is used: the first stage vacuum is -0.03~-0.05MPa and maintained for 60-90s, the second stage vacuum is -0.05~-0.06MPa and maintained for 60-90s, and the third stage vacuum is -0.09~-0.098MPa and maintained for 120-180s; the dispensing speed is controlled at 5~15mm / min.

[0070] First, pretreatment involves adding an appropriate amount of wetting and dispersing agent to the adhesive solution, which reduces the contact angle between the adhesive solution and the aluminum foil wall, enhancing the capillary drive effect. During dispersion, many air bubbles are generated. To reduce the number of air bubbles present in the material itself and those remaining during mixing, this invention employs a vacuum preparation system to degas the resin colloid before dispensing. Specifically, the adhesive container is placed in a vacuum storage tank, and after reaching the ultimate vacuum level, it is maintained for a certain period, using negative pressure to extract the gas dissolved within the adhesive solution.

[0071] Degassing vacuum degree: -0.09--0.098MPa; degassing holding time: 30-60min; adhesive temperature: 25~35℃ (the viscosity can be reduced by appropriately increasing the temperature); when the increase in adhesive density after degassing is stable within ±0.5% of the set value, it is judged as qualified for degassing.

[0072] After compression and shaping, the honeycomb walls of ultrafine honeycomb aluminum are prone to plastic buckling, and the cross-sectional shape of the cavity changes from a regular hexagon to an irregular shape. In some areas, the wall may adhere or the cavity may be constricted, and the flow resistance of the adhesive increases sharply at this point, which can easily form unfilled dead zones.

[0073] Therefore, after compressing and shaping the ultra-fine honeycomb aluminum and before applying adhesive, the ultra-fine honeycomb aluminum undergoes a springback stabilization treatment. The honeycomb aluminum compressed to the target thickness is left to stand for 10-30 minutes under the constraint of a mold, allowing the elastic rebound of the aluminum foil to be fully released. After the honeycomb wall reaches a relatively stable geometric configuration under the constraint of the mold, adhesive is then applied.

[0074] During the glue-filling process, this invention employs a bottom-up filling method. The compressed ultrafine honeycomb aluminum is placed inside the vacuum glue-filling chamber, with the injection port located at the bottom and the outlet at the top. Under vacuum negative pressure, the glue is propelled upwards from the bottom, while air is expelled from the top. This directional filling prevents air from being trapped as the glue flows downwards under gravity.

[0075] This invention employs a stepped vacuum process during the glue injection process.

[0076] For ultra-fine apertures of 0.3-0.8mm, a segmented, stepped vacuum extraction method is further employed: First stage: -0.03MPa, maintain for 60-90 seconds; Second stage: -0.06MPa, maintain for 60-90s; Third segment: -0.09 to 0.098 MPa, maintain for 120-180 seconds.

[0077] Under low vacuum conditions, the tiny bubbles remaining in the cavity expand and loosen under a lower pressure difference, breaking their fixed state at the angle of the honeycomb wall. The tiny bubbles expand and float upwards. When the vacuum is raised to a high vacuum (above -0.09MPa), the air is quickly extracted using a large pressure difference.

[0078] The dispensing speed must be strictly controlled. Too fast a speed will cause the adhesive to splash and form bubbles, while too slow a speed may cause the adhesive to thicken prematurely within its service life, losing its impregnation ability. For pore sizes of 0.3-0.8mm, the specific speed determined by experiment based on the adhesive viscosity and the height of the ultra-fine honeycomb aluminum is 5-15mm / min, which is considered a safe dispensing speed.

[0079] Furthermore, during the glue-filling process in step S203, low-frequency micro-vibration is applied to the bottom of the vacuum glue-filling cavity. The vibration frequency is 20-50Hz and the amplitude is in the micrometer range, in order to reduce the wall friction resistance when the glue moves forward in the ultra-fine honeycomb cavity and promote the glue to pass through the necking area.

[0080] After the glue is poured, set the vacuum holding time and let the product stand in a vacuum for 30-60 seconds to allow the remaining tiny air bubbles enough time to float to the surface and break. Then release the vacuum and let it cure.

[0081] In the specific production process, the filling rate needs to be verified to ensure that it is not less than 95% and that there are no continuous through cavities.

[0082] This invention further discloses a detection method: Fill rate distribution: A certain number of ultra-fine honeycomb aluminum samples from each batch were X-ray scanned, and the fill rate distribution was statistically analyzed.

[0083] Filling status: The filling status of each cavity is determined by grayscale analysis.

[0084] Overall fill rate: The density method is used as an auxiliary detection method to measure the mass increment of ultrafine honeycomb aluminum before and after glue filling, and the result is divided by the theoretical full glue mass to obtain the overall fill rate.

[0085] Adhesive replenishment mechanism: For ultrafine honeycomb aluminum alloys found to have insufficient filling rate during testing, a secondary vacuum adhesive replenishment method can be used. After the first adhesive filling and curing, the ultrafine honeycomb aluminum alloy is placed back into the vacuum filling chamber, and a second filling is performed under a vacuum of -0.09MPa. The remaining gaps in the honeycomb cavity after the first filling are used as adhesive channels for replenishment. After the second adhesive replenishment, vacuum degassing is performed again, followed by natural curing. The secondary adhesive replenishment can effectively compensate for insufficient filling caused by premature thickening of the adhesive or local necking during the first filling.

[0086] In step S100, the thickness of the polyurethane cathodic electrophoresis deposited film is 30-50 μm, and the drying temperature is 160-180℃.

[0087] Preferably, the thickness of the polyurethane cathodic electrophoresis deposited film is 40 μm, and the drying temperature is 165~175℃.

[0088] S100 is subjected to polyurethane cathodic electrophoresis treatment on the outer surface of a 1.5mm high-strength steel substrate to form a 40μm polyurethane electrophoretic anti-corrosion layer 5.

[0089] In terms of corrosion protection, cathodic electrophoresis allows polyurethane resin particles to be directionally deposited onto the surface of high-strength steel under the influence of an electric field, forming a continuous, dense, and uniformly covered coating. The uniformity of coverage ensures that the edges, corners, and complex-shaped areas of the steel plate achieve a uniform film thickness. This coating provides a physical shield against corrosive media such as water, oxygen, and chloride ions, blocking their penetration paths to the steel substrate surface.

[0090] In terms of deformation following function, the flexible segmental structure of polyurethane endows the coating with a high elongation at break. When the high-strength steel layer 2 undergoes micro-plastic deformation under impact, the coating extends synchronously with the substrate without cracking or peeling.

[0091] In terms of interface pre-setting function, the polyurethane electrophoretic anti-corrosion layer 5 simultaneously constitutes a flexible interface transition layer between the high-strength steel layer 2, the outer polyurea elastic buffer layer 1, and the inner ultra-fine fully adhesive honeycomb aluminum layer 3. The polar groups of the electrophoretic coating undergo a dual combination of chemical bonding and physical anchoring with the hydroxyl groups and oxide layer on the steel surface, forming a solid interface foundation. Subsequently, in S300, polyurea is sprayed onto the surface of the polyurethane electrophoretic anti-corrosion layer 5, and the honeycomb aluminum layer is bonded to the other side of the polyurethane electrophoretic anti-corrosion layer 5, both using the polyurethane electrophoretic anti-corrosion layer 5 as the interface anchor point. If this polyurethane electrophoretic anti-corrosion layer 5 is not present and polyurea is directly sprayed or honeycomb is bonded directly onto the exposed steel plate, the steel surface lacks polar groups, and interface debonding is likely to occur under impact.

[0092] In step S300, the spraying is high-pressure airless spraying, with multiple thin layers superimposed. The thickness of a single spray is 0.1-0.4 mm, and the cumulative total thickness is 0.5-1.2 mm. The construction environment temperature is 20-30℃, the interval between each spray is 10-20 minutes, and the curing time is 30-60 minutes at room temperature. The bonding and lamination process is as follows: integral roller pressing with 0.2-0.6MPa and low-temperature pre-curing at 60-80℃ for 60-120 minutes.

[0093] Preferably, the spraying is high-pressure airless spraying, with multiple thin layers stacked, each spray thickness being 0.2-0.3 mm, and the cumulative total thickness being 0.9 mm; the construction ambient temperature is 22-28℃, the interval between each spray is 15 minutes, and the curing time is 40 minutes at room temperature; The bonding and lamination process involves integral roller pressing with a pressure of 0.3-0.5 MPa and pre-curing at a low temperature of 65-75℃ for 90 minutes.

[0094] S300 includes two parallel operations: spraying polyurea onto one side of the high-strength steel layer 2 to form a polyurea elastic buffer layer 1, and bonding the ultra-fine fully adhesive honeycomb aluminum layer 3 to the other side of the high-strength steel layer 2.

[0095] The polyurea elastic buffer layer 1 serves as the outermost impact receiving layer. In step S300, it is first coated with multiple thin layers using a high-pressure airless spraying device. Polyurea has a fast reaction speed, and the two components complete gel curing within seconds after mixing in the spray gun. By using multiple thin layers with a 15-minute interval between each coat, the previous coating is partially cured before the next coat is applied, forming chemical bonds between the layers and resulting in a uniform and dense overall curing.

[0096] The ambient temperature during construction should be controlled between 22-28℃.

[0097] The fully adhesive-bonded honeycomb aluminum layer is bonded to the inner side of the high-strength steel layer 2 using an integral roll-pressing bonding method. Roll-pressing applies uniform pressure between the honeycomb aluminum layer and the electrophoretic steel layer, allowing the adhesive to fully wet the electrophoretic coating on the steel surface, eliminating tiny air bubbles at the interface, and forming a continuous bond throughout the entire area.

[0098] The rolling pressure needs to be controlled within a reasonable range: if the pressure is too low, the interface will not be sufficiently wetted and there will be micro-voids; if the pressure is too high, the honeycomb aluminum layer may be locally compressed and deformed, destroying the established full glue filling structure.

[0099] The purpose of low-temperature pre-curing is to initially shape the bonding interface, establish preliminary bonding strength between the honeycomb aluminum layer and the steel layer, and provide a stable operational basis for subsequent S400 hot-pressing composite.

[0100] After S300 is completed, a continuous interface system is formed in the three-layer composite material. The polyurethane electrophoretic anti-corrosion layer 5 serves as a through-interface layer, simultaneously acting as the adhesion substrate for the outer polyurea elastic buffer layer 1 and the bonding substrate for the inner honeycomb layer. This allows the stress concentration at the interface to be buffered by the flexible deformation of the polyurethane electrophoretic anti-corrosion layer 5 when impact loads are transferred from the polyurea elastic buffer layer 1 to the high-strength steel. Similarly, when the high-strength steel transfers loads to the honeycomb layer, the polyurethane electrophoretic anti-corrosion layer 5 provides a flexible transition, avoiding abrupt stress changes at the rigid interface.

[0101] In step S400, the hot pressing temperature is 65-85℃, the pressure is 0.3-0.5MPa, and the holding pressure is 40-90min; after the composite is completed, it is kept at a constant temperature for 12-36h.

[0102] Preferably, the hot pressing temperature is 70-80℃, the pressure is 0.4MPa, and the pressure holding time is 60min; after the composite is completed, it is kept at a constant temperature for 24h.

[0103] S400 hot-presses the PA fiberglass backing layer 4 onto the inner side of the honeycomb aluminum layer of the three-layer composite material to form the final four-layer structure.

[0104] This step uses a hot-pressing temperature of 70-80℃, a pressure of 0.4MPa, and a holding time of 60 minutes.

[0105] From a material compatibility perspective, PA fiberglass backing layer 4 is PA fiberglass backing layer 4, and the melting temperature of PA is typically above 220℃. At 70-80℃, the PA substrate will not melt and flow, therefore the interlayer bonding cannot rely on the melt bonding of PA.

[0106] This invention utilizes hot-pressing temperature and pressure to achieve interfacial bonding between the PA fiberglass backing layer 4 and the honeycomb aluminum layer through the adhesive interface of the honeycomb aluminum layer, while simultaneously avoiding thermal damage to the formed honeycomb full-fill structure and the polyurethane electrophoretic anti-corrosion layer 5 caused by high temperatures. If the hot-pressing temperature is too high, the resin colloid inside the honeycomb cavity may soften or even reflow due to heat, destroying the established full-fill structure. The polyurethane electrophoretic anti-corrosion layer 5 may also become over-crosslinked at high temperatures, losing its flexibility and deformation-following ability.

[0107] The purpose of holding the pressure for 60 minutes is to allow the interface between the PA fiberglass backing layer 4 and the honeycomb aluminum layer to fully contact, wet, and cure under constant pressure.

[0108] After S400 is completed, the PA fiberglass backing layer 4 is bonded to the bottom inner side of the honeycomb aluminum layer. Under subsequent impact conditions, when the honeycomb aluminum layer undergoes progressive plastic buckling collapse and attempts to expand laterally, the PA fiberglass backing layer 4 constrains the bottom of the honeycomb aluminum layer through its own in-plane stiffness and interlayer bond strength.

[0109] Without the PA fiberglass backing layer 4, the lateral expansion of the honeycomb aluminum layer under impact is unrestrained, and the honeycomb cells may break apart before reaching the energy absorption limit, and the impact energy cannot be fully dissipated. The presence of the PA fiberglass backing layer 4 locks the deformation range of the honeycomb aluminum layer within a controlled range, ensuring that the plastic buckling process of the honeycomb aluminum layer is gradual and stable, rather than instantaneous and unstable.

[0110] Further examples are provided below: Example 1

[0111] 1. Pretreatment of high-strength steel substrate and polyurethane cathodic electrophoresis molding A 1.5mm thick high-strength steel substrate (grade HC340LA) was selected, cut, leveled, and deburred. It was then subjected to alkaline washing and degreasing (NaOH concentration 3%, temperature 55℃, time 5min) and multi-stage pure water rinsing (conductivity ≤10μS / cm) to remove surface oil and impurities.

[0112] A polyurethane cathodic electrophoresis process was employed, using a polyurethane-modified epoxy resin cathodic electrophoretic coating as the electrophoresis bath solution (20% solids content, pH 5.8-6.2, conductivity 1200-1500 μS / cm). The electrophoresis voltage was 180V, the electrophoresis time was 120s, and the deposited film thickness was controlled at 40μm. After electrophoresis, the film was dried and cured at 165-175℃ for 30min, and then naturally cooled to room temperature to obtain a flexible, corrosion-resistant steel substrate with deformation-following properties.

[0113] 2. Ultra-fine honeycomb aluminum compression shaping and vacuum full glue filling Using virgin ultrafine honeycomb aluminum blanks with a pore size of 0.5mm (aluminum foil thickness 0.02mm, H18 fully hard state), the blanks are compressed and shaped by uniform pressure in a closed mold, with the overall thickness precisely controlled to 3.4mm after compression. After compression, the blanks are left to stand for 20 minutes under the constraint of the mold to allow the elastic rebound of the aluminum foil to be fully released, and the honeycomb wall to achieve a stable geometric configuration.

[0114] Pretreatment of the adhesive: Take 100 parts by weight of bisphenol A type epoxy resin E51 (epoxy value 0.51), add 30 parts by weight of curing agent polyetheramine D230, and 126 parts by weight of wetting and dispersing agent BYK-W901 (based on the total mass of the resin colloid). After stirring evenly, place it in a vacuum storage tank, evacuate to -0.095 MPa, maintain for 45 min, and perform vacuum degassing treatment. After degassing, the density increase of the adhesive is stable within ±0.5% of the set value.

[0115] Springback stabilization treatment: The compressed ultrafine honeycomb aluminum is left to stand for 20 minutes under the constraint of the mold to stabilize the geometric configuration of the honeycomb wall.

[0116] Vacuum potting: The settled ultrafine honeycomb aluminum is placed in the vacuum potting chamber, with the injection port at the bottom of the honeycomb block and the outlet at the top. A stepped vacuum system is used: the first stage is -0.04 MPa held for 75 seconds, the second stage is -0.06 MPa held for 75 seconds, and the third stage is -0.095 MPa held for 150 seconds. The adhesive is propelled upwards from the bottom under vacuum, with the injection speed controlled at 10 mm / min.

[0117] During the glue-filling process, low-frequency micro-vibration (35 Hz, 5 μm amplitude) is applied to the bottom of the vacuum glue-filling chamber. After glue filling, the chamber is left to stand under vacuum for 45 seconds to allow any remaining micro-bubbles to float and burst, after which the vacuum is released. The honeycomb cavity filling rate is ≥95%, with no continuous through cavities and no visible glue-deficient areas.

[0118] 3. Polyurea elastic buffer layer 1 spraying and three-layer composite On one side of the high-strength steel layer 2 (the surface of the polyurethane electrophoretic anti-corrosion layer 5), a polyurea elastic buffer layer 1 was sprayed using a high-pressure airless spraying device. The polyurea was an aliphatic polyurea (component A: isocyanate prepolymer, NCO content 16%; component B: amino polyether and chain extender), with an A / B volume ratio of 1:1. Multiple thin-layer coatings were applied, with a single coating thickness of 0.25 mm, and three coatings were applied for a cumulative total thickness of 0.9 mm. The ambient temperature was 25℃, with a 15-minute interval between each coating, and curing at room temperature for 40 minutes.

[0119] The ultrafine fully adhesive honeycomb aluminum layer 3 is precisely aligned with the other side (the surface of the polyurethane electrophoretic anti-corrosion layer 5) of the high-strength steel layer 2, and the entire composite material is obtained by integral roll pressing with 0.4MPa and pre-curing at a low temperature of 65~75℃ for 90 minutes. This achieves high-strength bonding throughout the entire area.

[0120] 4. PA fiberglass backing layer 4 Low-temperature hot-pressing composite Thermoplastic PA6 fiberglass composite sheet (30wt% fiberglass content, 1.0mm thickness) was bonded to the bottom inner side of the honeycomb aluminum layer. Hot-pressing was performed at 75℃, 0.4MPa, and held for 60 minutes to complete the four-layer integrated composite structure. After lamination, the sheet was left to stand at a constant temperature for 24 hours to fully release the internal stress of the composite.

[0121] Example 2

[0122] The only difference between this embodiment and Embodiment 1 is that a virgin ultrafine honeycomb aluminum blank with a pore size of 0.4 mm is used, and the overall thickness after compression remains 3.4 mm. All other steps, reagents, and parameters are the same as in Embodiment 1.

[0123] Example 3

[0124] The only difference between this embodiment and Embodiment 1 is that a virgin ultrafine honeycomb aluminum blank with a pore size of 0.6 mm is used, and the overall thickness after compression remains 3.4 mm. All other steps, reagents, and parameters are the same as in Embodiment 1.

[0125] Comparative Example This comparative example provides a three-layer composite structure, which differs from Example 1 in that: the PA fiberglass backing layer 4 is omitted, and only a three-layer structure (with a pore size of 4.0 mm) is prepared, consisting of a polyurea elastic buffer layer 1, a high-strength steel layer 2 (excluding the polyurethane electrophoretic anti-corrosion layer 5), and a honeycomb aluminum layer.

[0126] The integrated composite panels described in the above embodiments and comparative examples were subjected to CNC edge trimming, hole drilling, and shaping. Samples were then subjected to bottom ball impact testing, interlayer peeling testing, gravel impact testing, filler content distribution detection, filler state detection, overall filler content detection, and bonded area detection.

[0127] The detection method is as follows: 1. Bottom ball impact performance test Reference standards: Refer to the falling ball impact principle of GB / T39814-2021 "Test Method for Impact Strength of Ultra-thin Glass - Falling Ball Impact Method" and the equipment requirements for bottom ball impact testing of batteries in JJF (Mechanical) 1142-2025 "Calibration Specification for Bottom Ball Impact Tester of New Energy Vehicle Battery".

[0128] Test steps: 1. Sample preparation: Cut a 150mm×150mm sample from the integrated composite board, with at least 3 parallel samples per group.

[0129] 2. Equipment setup: Fix the sample horizontally on the sample fixture of the falling ball impact tester with the PA fiberglass backing layer 4 facing down and the polyurea elastic buffer layer 1 facing up, ensuring that the sample is rigidly constrained on all sides.

[0130] 3. Impact parameters: A steel ball with a diameter of 30mm (simulating the impact of the ball) and a mass of approximately 110g was selected. The impact energy was adjusted to achieve the target value by adjusting the drop height of the ball.

[0131] 4. Perform the impact: Release the steel ball and allow it to fall freely and impact the central region of the specimen. Each specimen is impacted only once.

[0132] Result evaluation: Energy absorption determination: Record whether the sample breaks down after impact (whether the steel ball penetrates the plate). If it does not break down, the energy level is considered passed.

[0133] Structural integrity check: After impact, the sample is visually inspected and examined under a low-power microscope to record whether there are through cracks, delamination, debonding, hollowing, or other phenomena.

[0134] 2. Interlayer peel strength test Reference standard: Refer to GB / T2790-2022 "Test method for peel strength of adhesives (90° peel)".

[0135] Test steps: Sample preparation: Cut strip-shaped samples with a width of 25 mm and a length of not less than 150 mm from the plate. At one end of the sample, carefully use a blade to pre-separate the interface between the polyurea elastic buffer layer 1 and the high-strength steel layer 2 by about 30 mm, as the peeling start end.

[0136] Clamping: Clamp the pre-separated polyurea elastic buffer layer 1 in the upper clamp of the tensile testing machine, and clamp the high-strength steel layer 2 (together with the remaining structure) in the lower clamp, ensuring that the peeling angle is 90°.

[0137] Test: Peel at a rate of 100 mm / min and record the force-displacement curve during the peeling process.

[0138] Data processing: Take the average force value of the stable peeling stage in the curve, divide it by the sample width, and obtain the interlayer peel strength (unit: N / mm).

[0139] 3. Stone impact test Reference standard: SAE J400-2012.

[0140] Test steps: Sample preparation: Cut a 100mm×100mm sample and use the surface of the polyurea elastic buffer layer 1 as the impact surface.

[0141] Equipment parameters (taking SAE J400 method B as an example): Sample pretreatment temperature: 5.6℃, pretreatment time: 15min. Impact angle: 90°. Impact pressure: 483kPa.

[0142] Stone type: pebble, size 9.53mm-15.86mm.

[0143] Number of stones: 1 pt (approximately 0.5 L), Number of impacts: 1.

[0144] Test execution: Fix the sample in the stone impact tester and spray stone according to the above parameters.

[0145] Results evaluation: After the impact, surface debris was removed, and the impacted area was photographed. Image analysis software was used to measure the area of ​​paint film damage (i.e., the area where the polyurea elastic buffer layer 1 was punctured, exposing the underlying steel substrate).

[0146] 4. Fill rate distribution detection (X-ray method) Reference Standard: Refer to ASTM E2662-09, "Standard Implementation Procedure for X-ray Inspection of Flat Composite Materials and Sandwich Cores for Aerospace Vehicles," which is explicitly applicable to the detection of pores / voids in honeycomb core materials.

[0147] Test steps: Equipment: Microfocus X-ray real-time imaging system.

[0148] Parameter settings: tube voltage 59kV, tube current 167μA (refer to X-ray inspection parameters for similar composite materials).

[0149] Scanning: The sample is placed between the X-ray source and the detector to perform a two-dimensional transmission scan or a three-dimensional CT scan.

[0150] Grayscale analysis: In the obtained X-ray images, the X-ray attenuation levels differ between the resin-filled areas and the cavity areas, resulting in different grayscale values. Image analysis software was used to extract the grayscale values ​​of each honeycomb cavity.

[0151] Distribution statistics: Set a grayscale threshold and count the proportion of cavity area with grayscale values ​​below the threshold, which is the unfilled rate of that area.

[0152] 5. Filling status inspection (ultrasonic method) Reference standard: Refer to ASTM E2580-24, "Standard implementation procedure for ultrasonic testing of flat composite materials and sandwich core materials used in aerospace applications".

[0153] Test steps: Equipment: Ultrasonic C-scan system, equipped with a 10MHz spherical focused immersion transducer (refer to parameters for similar adhesion detection).

[0154] Coupling: A water spray coupling method is used to prevent liquid from entering the honeycomb cavity.

[0155] Scanning: Perform a C-scan on the sample and record the amplitude of the reflected ultrasonic signal at the interface of the honeycomb layer.

[0156] Status determination: Completely filled: The acoustic impedance is well matched between the resin colloid, the honeycomb wall, and the high-strength steel layer 2, resulting in a low and uniform amplitude of the reflected signal.

[0157] Unfilled / Bubble-filled: A significant difference in acoustic impedance exists between the cavity or bubble and the resin, resulting in a strong reflected signal. On a C-scan image, this appears as an abnormally bright area.

[0158] 6. Overall fill rate test (density method) Reference standard: Refer to the density method for determining the volume content of fiber in composite materials.

[0159] Test steps: Sample preparation: Cut a sample of a regular shape (e.g., 50mm × 50mm), accurately measure its side length and thickness, and calculate the apparent volume V. apparent .

[0160] Mass measurement: The initial mass m of the sample was measured using a precision balance. initial .

[0161] Theoretical full-resin quality calculation: Given the density ρ of honeycomb aluminum Al The density ρ of the resin colloid resin And the compressed volume of the honeycomb aluminum.

[0162] The formula for calculating the theoretical full-resin quality is shown in Equation I: .............Formula I Among them, V Al V is the volume of the aluminum foil. cavity This represents the total volume of the honeycomb cavity.

[0163] The formula for calculating the actual filling mass is shown in Equation II: Formula II Where, m Al The known mass of the honeycomb aluminum.

[0164] The formula for calculating the fill rate is shown in Equation III: Formula III 7. Bonding area detection (ultrasonic C-scan method) Reference standard: Refer to the method of ultrasonic C-scan to detect the bonding quality, and determine the bonding and debonding areas by analyzing the interface reflection signal.

[0165] Test steps: Equipment and Scan: Use the same ultrasound C-scan system as for “filling status detection”, but adjust the depth of focus to the interface between the cellular layer and the steel layer or PA layer.

[0166] Signal Analysis: Good bonding area: When ultrasonic waves pass through a well-bonded interface, the reflected signal is weak (or the transmitted signal is strong).

[0167] Debonded / unbonded areas: There is an air gap at the interface, and the acoustic impedance difference is extremely large, which generates a strong reflected signal.

[0168] Area statistics: On a C-scan image, a threshold for the amplitude of reflected signals is set, and the percentage of pixel area below this threshold (i.e., good adhesion) is the adhesion area ratio.

[0169] Relative multiplier calculation: The bonding area ratio of the example is compared with that of the control sample (which can be prepared separately) using a conventional surface coating process, and the improvement factor is calculated.

[0170] The test results are shown in the table below.

[0171]

[0172] As can be seen from the data in the table: 1. The ball impact energy of Examples 1-3 is stably 1060-1090J, which is more than 35% higher than the 800J of the comparative example.

[0173] 2. After a 1090J ultimate impact, the plates in Examples 1-3 showed no puncture, no through cracks, no interlayer delamination in the four-layer structure, and no debonding or hollowing, while the comparative example showed localized cracking of the honeycomb layer and edge debonding.

[0174] 3. The polyurethane electrophoretic anti-corrosion layer 5 can follow the slight deformation of the steel plate without cracking, and the area of ​​paint film damage caused by gravel impact is reduced by 35% compared with epoxy electrophoresis.

[0175] 4. Compared with the traditional surface brushing process, the interlayer peel strength is improved by 12% by the full cavity potting composite process.

[0176] 5. The range of ball-hitting performance data for the product has been reduced from 120J to less than 20J, significantly improving batch stability.

[0177] 6. The bottom layer is made of thermoplastic PA glass fiber material, which can be melted, recycled and remanufactured, meeting the regulatory requirements for the recyclability of new energy vehicle parts.

[0178] 7. Full cavity potting increases the bonding contact area to 8-12 times that of traditional surface adhesive processes.

[0179] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. All such modifications or substitutions should be covered within the protection scope of this application, and should not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application. Therefore, the protection scope of this application should be determined by the protection scope of the claims.

Claims

1. A composite structure containing four layers of gradient energy absorption, characterized in that, From the outside to the inside, it includes: a polyurea elastic buffer layer (1), a high-strength steel layer (2), an ultra-fine fully glued honeycomb aluminum layer (3), and a PA fiberglass backing layer (4). The outer surface of the high-strength steel layer (2) is provided with a polyurethane electrophoretic anti-corrosion layer (5); The ultra-fine fully glued honeycomb aluminum layer (3) is disposed between the high-strength steel layer (2) and the PA glass fiber backing layer (4), and the honeycomb cavity of the ultra-fine fully glued honeycomb aluminum layer (3) is filled with resin colloid. The polyurea elastic buffer layer (1) is disposed on the outer surface of the polyurethane electrophoretic anti-corrosion layer (5); The polyurea elastic buffer layer (1), the high-strength steel layer (2), the ultra-fine fully glued honeycomb aluminum layer (3), and the PA glass fiber backing layer (4) form a gradient energy absorption synergistic structure that transmits energy step by step.

2. The composite structure containing four layers of gradient energy absorption according to claim 1, characterized in that, The thickness of the polyurea elastic buffer layer (1) is 0.5-1.2 mm; The thickness of the high-strength steel layer (2) is 1.0-2.0 mm; The thickness of the polyurethane electrophoretic anti-corrosion layer (5) is 30-50 μm; The ultrafine fully glued honeycomb aluminum layer (3) has a honeycomb pore size of 0.3-0.8 mm and a thickness of 2.5-4.5 mm after compression.

3. The composite structure containing four layers of gradient energy absorption according to claim 1, characterized in that, The resin colloid is epoxy resin or polyurethane resin; the PA fiberglass backing layer (4) is a PA fiberglass backing layer (4).

4. A method for preparing the four-layer gradient energy-absorbing composite structure according to any one of claims 1-3, characterized in that, Includes the following steps: S100. Provide a high-strength steel substrate, and perform polyurethane cathodic electrophoresis treatment on the outer surface of the high-strength steel substrate to form a polyurethane electrophoretic anti-corrosion layer, so as to obtain a high-strength steel layer. S200. Provide ultra-fine honeycomb aluminum, compress and shape the ultra-fine honeycomb aluminum, and then perform vacuum potting to fill the honeycomb cavity with resin colloid to form an ultra-fine fully glued honeycomb aluminum layer. S300. Spray polyurea on one side of the high-strength steel layer to form a polyurea elastic buffer layer, and bond the ultra-fine full-adhesion honeycomb aluminum layer to the other side of the high-strength steel layer to obtain a three-layer composite material. S400. The PA fiberglass backing layer is hot-pressed onto the ultrafine fully glued honeycomb aluminum layer of the three-layer composite material to obtain a four-layer gradient energy-absorbing composite structure.

5. The method according to claim 4, characterized in that, In step S200, the pore size of the ultrafine honeycomb aluminum is 0.3-0.8mm, and the overall thickness after compression is 2.5-4.5mm; the vacuum degree of the vacuum potting is -0.05~-0.098MPa, so that there are no continuous through cavities in the honeycomb cavity and no areas of missing glue that are visible to the naked eye. The fill rate of the honeycomb cavity is ≥95%.

6. The method according to claim 5, characterized in that, In step S200, the vacuum potting includes the following sub-steps: S201. Take the resin colloid, add 5-8% wetting and dispersing agent based on the total mass of the resin colloid, stir evenly, and then perform vacuum degassing treatment. The vacuum degree is -0.09--0.098MPa, and the treatment is maintained for 30-60 minutes. S202. After the ultra-fine honeycomb aluminum compressed to the target thickness is left to stand for 10-30 minutes under the constraint of the mold, the elastic rebound of the aluminum foil is fully released and the honeycomb wall reaches a stable geometric configuration before the glue is poured. S203. Place the settled ultra-fine honeycomb aluminum into the vacuum potting chamber. The potting port is set at the bottom of the ultra-fine honeycomb aluminum, and the outlet is set at the top. Under vacuum negative pressure, the adhesive is pushed upward from the bottom and the air is discharged from the top. During the dispensing process, a stepped vacuum is used: the first stage vacuum is -0.03~-0.05MPa and maintained for 60-90s, the second stage vacuum is -0.05~-0.06MPa and maintained for 60-90s, and the third stage vacuum is -0.09~-0.098MPa and maintained for 120-180s; the dispensing speed is controlled at 5~15mm / min.

7. The method according to claim 6, characterized in that, During the glue-filling process in step S203, low-frequency micro-vibration is applied to the bottom of the vacuum glue-filling cavity. The vibration frequency is 20-50Hz and the amplitude is in the micrometer range. This reduces the wall friction resistance when the glue moves forward in the ultra-fine honeycomb cavity and promotes the passage of the glue through the necking area.

8. The method according to claim 4, characterized in that, In step S100, the thickness of the polyurethane cathodic electrophoresis deposited film is 30-50 μm, and the drying temperature is 160-180℃. In step S300, the spraying is high-pressure airless spraying, with multiple thin layers superimposed. The thickness of a single spray is 0.1-0.4 mm, and the cumulative total thickness is 0.5-1.2 mm. The construction environment temperature is 20-30℃, the interval between each spray is 10-20 minutes, and the curing time is 30-60 minutes at room temperature. The bonding and lamination process is as follows: integral roller pressing lamination at 0.2-0.6MPa, and low-temperature pre-curing at 60-80℃ for 60-120 minutes; In step S400, the hot pressing temperature is 65-85℃, the pressure is 0.3-0.5MPa, and the pressure holding time is 40-90min; after the composite is completed, it is kept at a constant temperature for 12-36h.

9. The application of the four-layer gradient energy-absorbing composite structure according to any one of claims 1-3 or the four-layer gradient energy-absorbing composite structure prepared by the method according to any one of claims 4-8 in an automotive underbody protection plate, characterized in that, The vehicle underbody protection plate is used for the bottom protection of the battery pack in new energy vehicles.

10. The application according to claim 9, characterized in that, The four-layer gradient energy-absorbing composite structure is installed with the polyurea elastic buffer layer facing the outside of the vehicle and the PA fiberglass backing layer facing the inside of the passenger compartment.